2018
DOI: 10.30802/aalas-cm-18-000017
|View full text |Cite
|
Sign up to set email alerts
|

Allograft Inflammatory Factor 1 as an Immunohistochemical Marker for Macrophages in Multiple Tissues and Laboratory Animal Species

Abstract: Allograft inflammatory factor 1 (AIF1) is a commonly used marker for microglia in the brains of humans and some animal models but has had limited applications elsewhere. We sought to determine whether AIF1 can be used as a macrophage marker across common laboratory animal species and tissues. We studied tissues (that is, spleen, liver, and lung) with defined macrophage populations by using an AIF1 immunostaining technique previously validated in human tissue. Tissues were collected from various mouse strains (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…A key attribute of the Bge cell is its hemocyte-like phenotype, given the central role of the snail hemocyte in innate and cellular immunity. The allograft in ammatory factor 1 (AIF) is a conserved calcium-binding protein typically expressed in phagocytic and granular leukocytes and is a marker of macrophage activation [38,41,46,[61][62][63][64]. An orthologue, termed BgAIF, is highly expressed in isolates of B. glabrata that are resistant to infection with S. mansoni and it has been suggested that this gene may be linked to hemocyte activation [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…A key attribute of the Bge cell is its hemocyte-like phenotype, given the central role of the snail hemocyte in innate and cellular immunity. The allograft in ammatory factor 1 (AIF) is a conserved calcium-binding protein typically expressed in phagocytic and granular leukocytes and is a marker of macrophage activation [38,41,46,[61][62][63][64]. An orthologue, termed BgAIF, is highly expressed in isolates of B. glabrata that are resistant to infection with S. mansoni and it has been suggested that this gene may be linked to hemocyte activation [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…However, even though Bge cells adhere to the schistosome, the parasite is not killed by these cells in vitro. The allograft in ammatory factor 1 (AIF) is a conserved calcium-binding protein typically expressed in phagocytic and granular leukocytes and is a marker of macrophage activation (38,41,45,(62)(63)(64)(65). An orthologue, termed BgAIF, is highly expressed in isolates of B. glabrata that are resistant to infection with S. mansoni and this gene may be linked to hemocyte activation (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Last, morphological changes were not apparent between the However, even though Bge cells adhere to the schistosome, the parasite is not killed by these cells in vitro. The allograft inflammatory factor 1 (AIF) is a conserved calcium-binding protein typically expressed in phagocytic and granular leukocytes and is a marker of macrophage activation (38,41,45,(62)(63)(64)(65). An orthologue, termed BgAIF, is highly expressed in isolates of B. glabrata that are resistant to infection with S. mansoni and this gene may be linked to hemocyte activation (8,9).…”
Section: Programmed Mutation Of Bgaif Confirmed Functional Crispr/casmentioning
confidence: 99%